Government Policy and Equality of Income Distribution in the Netherlands (1945-1986) - van Wijngaarden, P. (Journal of Income Distribution®, 1992)
Inequality of income distribution in the Netherlands has since 1945 strongly been influenced by government policies. Until the end of the 1970s, governments pursued policies designed to reduce income differentials. The most important results were the construction of a social security system and the attainment of greater equality in the sphere of personal income distribution. In the 1980s, these policies were reversed. The earning discrepancies between groups of gainfully employed and the gap between the employed and unemployed were growing. There were drastic cuts in social security. In this paper, the most important instruments, policy instruments, and objectives, and their results are analyzed.